Arsenic, cadmium, lead and mercury levels in blood of Finnish adults and their relation to diet, lifestyle habits and sociodemographic variables - Abass,K; Koiranen,M; Mazej,D; Tratnik,JS; Horvat,M; Hakkola,J; Jarvelin,M-R; Rautio,A (Environmental Science and Pollution Research, 2016)
The Northern Finland Birth Cohort program (NFBC) is the epidemiological and longitudinal prospective general population research program, which was established to promote health and wellbeing of the population in northern Finland. The aim of present study, as a part of the NFBC program, was to analyze the blood levels of arsenic (B-As), cadmium (B-Cd), lead (B-Pb), total mercury (B-Hg) and selenium (B-Se); to compare these levels with threshold limits; to study sociodemographic factors; and to correlate these levels with calcium and haemoglobin. The study was comprised of 249 NFBC subjects, of which 123 were female and 126 were male (ages 31.1 ± 0.3 and 31.1 ± 0.4, respectively). All participants were asked to complete a questionnaire regarding diet and living habits. The geometric means (± SD) of B-As were 0.49 ± 2.80 μg/l and 0.44 ± 2.72 μg/l; B-Cd were 0.18 ± 4.02 μg/l and 0.12 ± 3.21 μg/l; B-Pb were 17.0 ± 1.8 μg/l and 9.06 ± 2.20 μg/l; B-Hg were 2.18 ± 2.02 μg/l and 1.85 ± 1.78 μg/l; and B-Se were 106.0 ± 1.3 and 94.3 ± 1.3 μg/l in males and females, respectively. Among the subjects in the present analysis, 23 % of males and 17.1 % of females had B-As levels above the ATSDR normal human levels of B-As in unexposed individuals (1.0 μg/l). The B-Pb geometric mean (12.44 μg/l) was approximately one eighth the CDC toxicological cut-off point of 100 μg/l. Twenty-one individuals (8.4 %) exceeded a B-Hg level of 5.8 μg/l. Fifty-eight females (47 %) had a B-Hg higher than 2.0 μg/l, the German Federal Environmental Agency cut-off point for women (18–69 years) who consume fish at least three times/month; therefore, their babies could be at risk of adverse effects during development.